Factors of Stress Amongst Students of Professional Institutes - Preet, Kamal; Ahluwalia, Amardeep Kaur (Prabandhan: Indian Journal of Management, 2019)
The study was conducted to identify factors of stress amongst (n = 428) students of the age group of 18 years-23 years studying in various professional institutes in the state of Punjab. There were 243 (56.77 %) boys, while 185 (43.22%) were girls. Data were collected by using a self administered questionnaire through convenience sampling method from Gurdaspur, Amritsar, Jalandhar, Ludhiana, and Chandigarh; 58% of the students (248) belonged to the graduate courses such as B.Com, B. Tech, BBA, BCA, LLB and 42% (180) of the students belonged to the post graduate courses such as MBA, M. Tech, MCA, and M.Com. The time period of the study was January-May 2018. Eight factors were extracted through factor analysis. The total variance explained was 68.13%. The first factor extracted was Daily Grind (13.308%) followed by Academic Pressure (11.653%), Peer Pressure (11.269 %), Family Pressure (7.746%), Personal Complexes (6.971%), and Financial Pressure (4.747%). There were three factors which seemed different relatively in terms of previous literature such as Daily Grind (13.308%), Procrastination (6.666%), and Materialism (5.780%). This indicated that the daily activities and chores amongst students were also a cause for huge stress due to time constraints. Further, the students who kept on delaying or postponing things for later got stressed out when work piled up. It was also observed that the increasing association of good living with materialistic things or money also gave rise to stress and depression amongst students.